HUBUNGAN VOLUME TEGAKAN DENGAN KANDUNGAN BIOMASSA TERSIMPAN SKALA PLOT PADA AREAL AGROFORESTRY DUSUNG DI DUSUN TOISAPU KOTA AMBON - latumahina, fransina sarah (Jurnal Pemuliaan Tanaman Hutan, 2019)
ABSTRACT The study was carried out in the Dusung Community Forest (Agroforestry) area of Toisapu Negeri Hutumuri Hamlet, South Leitimur Sub-District, Ambon City in August - October 2018 to determine the relationship between stand volume and stored biomass for scale plots in dusung agroforestry areas in Toisapu Hamlet. For this reason, it begins with an inventory of potential at seedling, sapling, pole and tree levels so that information and data on the actual potential of carbon content in the dusung system are obtained based on the value of the diversity of stand volume and biomass content. The results of the three measurement plots showed that the highest biomass was seen to be dominated by Durian, Pala and Langsat and Duku and Clove plants. Based on the calculation of the biomass value of the total carbon content in the three plots, it can be seen biomass potential for a total 400 m² plot area or 0.04 ha for the three plots with an area of 1,200 m² or 0.12 ha having a total biomass of 50,783.77 Kg / m² multiplied by the assumption of 0.5% of the total amount of tree biomass and poles so that the total carbon content stored in the three plots is 25,391.88 kg / m² or 2,539.19 tons / ha. Keywords: Agroforestry, Shelter Biomass, Dusung ABSTRAK Penelitian dilaksanakan pada areal Hutan Rakyat (Agroforestry) Dusung di Dusun Toisapu Negeri Hutumuri Kecamatan Leitimur Selatan Kota Ambon pada Bulan Agustus 2018 untuk menentukan hubungan antara volume tegakan dan kandungan biomasa tersimpan untuk skala plot pada areal agroforestry dusung di Dusun Toisapu. Untuk itu, diawali dengan menginventarisasi potensi pada tingkat semai, pancang, tiang dan pohon sehingga diperolehnya informasi dan data potensi aktual kandungan karbon pada sistem dusung berdasarkan nilai keragaman volume tegakan dan nilai kandungan biomassa. Hasil penelitian pada tiga plot pengukuran menunjukan bahwa biomasa tertinggi terlihat didominasi oleh jenis tanaman Durian, Pala dan tanaman Langsat serta Duku dan Cengkih. Berdasarkan perhitungan nilai biomassa terhadap jumlah kandungan karbon pada ketiga plot, terlihat potensi biomassa untuk total luas petak ukur 400 m² atau 0,04 ha untuk ketiga plot dengan seluas 1.200 m² atau 0,12 ha memiliki jumlah total biomassa 50.783,77 Kg/m² yang dikalikan dengan asumsi 0,5 % dari total jumlah biomassa pohon dan tiang sehingga jumlah kandungan karbon yang tersimpan pada ketiga plot sebesar 25.391,88 kg/ m² atau 2.539,19 ton/ha. Kata Kunci : Agroforestry, Biomassa, Dusung.